Role of magnesium in the efficacy of hypoglycemic agents - Huachin, Fernando (1995)
We wanted to demostrate that magnesium deficiency inhibits basal or exogenous insulin and oral hypoglycemic stimulated glucose utilization. Soleal muscle was removed from twenty-one albine rats (250-300 g) for incubation in Ringer-Krebs media in the presence or absence of magnesium and with a known quantity of glucose (6x10³ mol/L). Samples were studied with spectophotometer before and after incubation with enzymatic glucose. The study involved three stages: in the first, we observed calcium and magnesium interaction; in the second, insulin interaction; and in the third interaction with oral hypoglycemic agents, chlorpropamide and glybenclamide. With basal and exogenous insulin we observed more muscle utilization of glucose in the media that contained calcium and magnesium than in those with calcium but no magnesium. With sulphonilureas interaction there was a decrease of glucose utilization in the medium without magnesium, more with first than second generation sulphonilurea. These results suggest that both tissue utilization of basal glucose and glucose stimulated by hypoglycemic agents depend on magnesium concentration and are decreased with hypomagnesemia.